Sportorthopädie - Köhler H-P; Polenz C; Witt M (Deutsche Zeitschrift für Sportmedizin, 2017)
Background: While the contribution of the limbs topropulsion in freestyle swimming is well established,the important role of the trunk with its functions as support and impulse generator is often underestimated. Two different trunk movement techniques can be observed, the body-roll and the twist-technique. There is a lack of information about the quantitative differences between these two techniques. The aim of the study was to examine differentiation characteristics using sensor-based information and to observe changes with increasing speed.Methods: 27 athletes took part in the study,swimming in five different speed ranges. Four inertial measuring units recorded their trunk movements. Results: With increasing speed,the range of motion of the shoulder decreasesfrom 120 to 95. In addition, the range of motion of the hip decreasesfrom 86 to 46. The mean speed of rotation of the shoulder increasesfrom 125/s to 180/s while rotation speed of the shoulder stays equal. The phase shift, as an expression of the gap of both segments changing the direction, increases from 0.04s to 0.08s.Conclusions: The results did not provide evidence for a clear, distinct definition of the two techniques. Rather, hereis a fluent transition with increasing speed from the body-roll to the twisttechnique. The twist-technique, in combination with insufficient core stability, can represent an increased injury potential.KEY WORDS: Freestyle Swimming, Trunk Movements, Inertial Measuring Unit, Core Stability, Spine Injury